Hadis sebagai Sumber Ajaran (Nāṣir dan Inkār al-Sunnah) - Jamaluddin, Jamaluddin (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This research aims to comprehensively analyze the Sunnah as a source of Islamic Law and will explain the meaning of nāṣir and inkār al-Sunnah. This research uses a type of library research because this study completely requires a review of the written works of experts related to the discussion. This research is also normative because it will examine the texts of the Koran and Hadith or the thoughts of scholars related to the discussion. The results of this research found that the ulama agreed that the sunnah was the source of Islamic teachings after the Koran. Inkār al-Sunnah is an understanding that rejects the blasphemy of the Sunnah as a source of Islamic law and this understanding is divided into two groups, namely: first, rejecting all hadith as jahah; second, only accepting mutawatir hadith as proof. One of the factors causing understanding is a lack of knowledge, especially in the field of hadith science.